P-233 Dying to work together – partnership and potential. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Arnold, Liz; Moody, Shane
Abstract : ' The path to successful partnerships is littered with many attempts that have failed ' (Mitchell & Karoff, 2015). Over a period of more than a decade, the hospice had an in-reach specialist palliative care team working in the local hospital, during which time the hospital developed its own end of life care team. Both teams worked in isolation, challenged by different structures, values and approaches. It became clear that expectations regarding leadership, goals, roles, processes and responsibilities of partnership working differed significantly. The concept of the two teams working collaboratively was strong, but many challenges soon emerged. Joining forces to make a difference was not going to be an easy prospect. We had not aligned our values and as a result, became disconnected in our day-to-day interactions to such an extent that it was on the threshold of being unsustainable. In October 2018, the Trust appointed a Clinical Director for End of Life Care and this was the beginning of the integration of the two teams. Together with the Director of Nursing from the hospice, leadership of this team is based on trust in each other's ability to lead effectively and with integrity. One of the early pieces of work we commenced together was to acknowledge the two organisations values, missions and operating principles and collectively agree our operational values and behaviours moving forward. For this partnership to be successful, it will require strong leadership, common understanding, a shared vision and purpose, mutual understanding and an acceptance of differences. It will require resilience in the face of inherent tensions and inevitable conflict. Partners frustrate each other; partners will let each other down – if we can accept these challenges and work with them, together we have a much better chance of making a difference.